Personnel, equipment, and facilities for electrophysiological and catheter ablation procedures in Europe: results of the European Heart Rhythm Association Survey. Issue 7 (July 2014) - Estner, Heidi L.; Chen, Jian; Potpara, Tatjana; Proclemer, Alessandro; Todd, Derick; Blomström-Lundqvist, Carina; ,
Abstract : Clinical electrophysiology (EP) and catheter ablation of arrhythmias are rapidly evolving in recent years. More than 50 000 catheter ablations are performed every year in Europe. Emerging indications, an increasing number of procedures, and an expected high quality require national and international standards as well as trained specialists. The purpose of this European Heart Rhythm Association (EHRA) survey was to assess the practice of requirements for EP personnel, equipment, and facilities in Europe. Responses to the questionnaire were received from 52 members of the EHRA research network. The survey involved high-, medium-, and low-volume EP centres, performing >400, 100–399, and under 100 implants per year, respectively. The following topics were explored: (i) EP personnel issues including balance between female and male operators, responsibilities within the EP department, age profiles, role and training of fellows, and EP nurses, (ii) the equipments available in the EP laboratories, (iii) source of patient referrals, and (iv) techniques used for ablation for different procedures including sedation, and peri-procedural use of anticoagulation and antibiotics. The survey reflects the current EP personnel situation characterized by a high training requirement and specialization. Arrhythmia sections are still most often part of cardiology departments and the head of cardiology is seldom a heart rhythm specialist. Currently, the vast majority of EP physicians are men, although in the subgroup of physicians younger than 40 years, the proportion of women is increasing. Uncertainty exists regarding peri-procedural anticoagulation, antibiotic prophylaxis, and the need for sedation during specific procedures.